365 moral stories - Om Kidz (Noida : Om Kidz, 2023)
Stories don't just transport us into a world of imagination; they teach us good morals too. 345 moral Stories bring forth a special story for each day of the year and a lesson to learn with it. Immerse yourself into the wonderful world of stories and learn A new moral each day! After 365 stories, you're bound to learn a lot! Let the reading- and the learning -begin!.
Keywords: Stories